Advances in Body Area Networks I Post-Conference Proceedings of BodyNets 2017 - Fortino, Giancarlo; Wang, Zhelong; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the post-proceedings, including all revised versions of the accepted papers, of the 2017 European Alliance for Innovation (EAI) International Conference on Body Area Networks (BodyNets 2017). The goal of BodyNets 2017 was to provide a world-leading and unique forum, bringing together researchers and practitioners from diverse disciplines to plan, analyze, design, build, deploy and experiment with/on Body Area Networks (BANs).
Keywords: Telecommunication; Application software; Biomedical engineering; Communications Engineering, Networks; Computer and Information Systems Applications; Biomedical Engineering and Bioengineering